2012
DOI: 10.4236/as.2012.34074
|View full text |Cite
|
Sign up to set email alerts
|

Outlook of future climate in northwestern Ethiopia

Abstract: Climate change is described as the most universal and irreversible environmental problem facing the planet Earth. While climate change is already manifesting in Ethiopia through changes in temperature and rainfall, its magnitude is poorly studied at regional levels. The objective of this paper was to assess and quantify the magnitude of future changes of climate parameters using Statistical Downscaling Mode (SDSM) version 4.2 in Amhara Regional State which is located between 8°45‘N and 13°45‘N latitude and 35°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…A trend of seasonality in peak childhood diarrhea cases, which occurred more frequently from January to March and April to June, was also observed. In the study area, the period between January and March is a dry season and April to June is the beginning of the rainy season, both of which exhibit high temperatures compared to other months [ 56 ]. This finding is consistent with previous studies [ 21 , 57 62 ] that showed climate factors significantly affected seasonal childhood diarrhea, with more cases observed during the periods of high temperature and drier months of the year, for a number of reasons.…”
Section: Discussionmentioning
confidence: 99%
“…A trend of seasonality in peak childhood diarrhea cases, which occurred more frequently from January to March and April to June, was also observed. In the study area, the period between January and March is a dry season and April to June is the beginning of the rainy season, both of which exhibit high temperatures compared to other months [ 56 ]. This finding is consistent with previous studies [ 21 , 57 62 ] that showed climate factors significantly affected seasonal childhood diarrhea, with more cases observed during the periods of high temperature and drier months of the year, for a number of reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The area is highly productive and consistent daily climate data are important for various impact studies. Existing studies which involve the study of weather and climate suffer from insufficient weather data which restricts them to rather small areas (Bewket and Conway, ; Ayalew, ; Ayalew et al , ; Taye and Zewdu, ). For example Taye et al () used data from coarse global and regional climate models for the assessment of effects of climate change on the Lake Tana catchment (15 000 km 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical details of this model are provided in the study by Wilby et al [38]. As the values are normally distributed, transformation was not undertaken on temperature results in the software [18]. However, for the daily rainfall, the fourth root transformation was used as the data were skewed and as its model was conditional.…”
Section: Downscaling Methodsmentioning
confidence: 99%
“…In Ethiopia, we have explored various downscaling applications and their potential to detect climate change impacts in agricultural and hydrological applications. Some of these applications include statistical downscaling for daily temperature and rainfall in South Wollo [17], the study of future changes in climate parameters in Amhara Regional State [18], future climate studies in northwestern Ethiopia for assessing the hydrological response of the Gilgel Abay River to climate change in the Lake Tana Basin [19], and the climate change impact on the Geba Catchment in Northern Ethiopia [20]. However, applications of statistical downscaling of general circulation models for the largest cities in Ethiopia have not been undertaken.…”
Section: Introductionmentioning
confidence: 99%